2018
DOI: 10.1002/lio2.136
|View full text |Cite
|
Sign up to set email alerts
|

Completion lymphadenectomy for sentinel node positive cutaneous head & neck melanoma

Abstract: The application and utility of melanoma sentinel lymph node biopsy (SLNB) has evolved significantly since its inception over two decades ago. The current focus has shifted from a staging modality to potentially a therapeutic intervention. Recent research to include large multi‐institutional randomized trials have attempted to answer the question: is a completion lymph node dissection (CLND) required following a positive SLNB? This review provides an evidence‐based, contemporary review of the utility of CLND fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…Patients in our study with head and neck melanoma were also sig- specific survival after CLND. 12,13 Second, the head and neck region includes many crucial structures in close proximity, 14 thus making a nodal recurrence potentially more morbid and technically more challenging. 15 Third, lymphedema after modified radical neck dissection lymph node dissection for head and neck cancer is less common, making the procedure less morbid overall.…”
Section: Head and Neck Primarymentioning
confidence: 99%
See 1 more Smart Citation
“…Patients in our study with head and neck melanoma were also sig- specific survival after CLND. 12,13 Second, the head and neck region includes many crucial structures in close proximity, 14 thus making a nodal recurrence potentially more morbid and technically more challenging. 15 Third, lymphedema after modified radical neck dissection lymph node dissection for head and neck cancer is less common, making the procedure less morbid overall.…”
Section: Head and Neck Primarymentioning
confidence: 99%
“…15 Third, lymphedema after modified radical neck dissection lymph node dissection for head and neck cancer is less common, making the procedure less morbid overall. 13,14 Although many studies do in fact report lymphedema in head and neck cancer patients, no robust studies looking at lymphedema-related quality of life in head and neck melanoma patients have been performed. 16 Fourth, melanoma of the head and neck portends a worse prognosis compared with other sites.…”
Section: Head and Neck Primarymentioning
confidence: 99%
“…Likewise, our study suggests that MSLT‐II's conclusions similarly warrant intense scrutiny before abandoning H&N iCLND, which may increase CN injury frequency and severity . Unfortunately, a sufficiently powered prospective HNCM study examining the efficacy of SLNB with immediate NSLN excision versus observation is unlikely . However, our study shows that SLNB‐guided regional nodal management of cN0 HNCM is highly efficacious, evidenced by 85.4% regional disease control with 4.9 years of median follow‐up.…”
Section: Discussionmentioning
confidence: 73%
“…The crucial importance of regional nodal metastasis for prognostication, disease recurrence, and survival in melanoma is well supported with prospective data reflected by The American Joint Committee on Cancer (AJCC) staging and the National Comprehensive Cancer Network (NCCN) treatment guidelines . Sentinel lymph node biopsy (SLNB) is recommended for cN0 T2–T4 and select T1b melanomas, and until recently immediate completion lymph‐node dissection (iCLND) was recommended following all positive SLNBs . The initial Multicenter Selective Lymphadenectomy Trial (MSLT‐I) demonstrated that SLNB followed by iCLND among patients with regionally metastatic melanoma confers prolonged disease‐free survival (DFS) and melanoma‐specific survival (MSS) over observation .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation